Production RAW Material Inventory Control Information System at PT. SIIX EMS Indonesia - Tukino; Shofa Shofia Hilabi; Heri Romadhon (Buana Information Technology and Computer Sciences (BIT and CS), 2020)
Application of web-based raw material inventory control information system with a bill of materials (BOM) using the PHP and MySQL programming language as a database, and using the SDLC livestock device engineering method with stages of planning, design, implementation, and testing. I create a recording application that provides information about the availability of raw material reducing the error in calculating the amount of raw material based on the bill of material. With this application, it can help to purchase in determining the number of raw materials needed for production based on the master bill of material data.